Stabilisation and stability operations : a Literature Review - Fitz-Gerald, Ann; Blair, Stephanie (Cranfield University, 2010)
‘Stabilisation’, ‘stability operations’ and ‘instability’ are relatively new terms in the conflict transformation lexicon and the literature on these areas has grown significantly over a fairly short time period. For better or for worse, knowledge in this area has been shaped predominantly by the formative experiences in Afghanistan and Iraq. These operations are based on a view that weak and failing states pose a direct threat to wider international and national security. This article provides a literature survey which takes this sentiment and these two significant operations as its points of departure, particularly in light of the significance of 9/11 as a defining moment in thinking about international security and the nature of the international system. One trend has been to situate analyses of stability operations in the broader context of instability and fragile states, with early warning and statebuilding as core concepts, and in part formed by the experiences of counter-insurgency and its attendant military doctrine. Notwithstanding these experiences, the literature on stabilisation operations has not yet matured sufficiently to join with related areas of research in a more systematic and explicitly theoretical way. Nor has a systematic, academic and referenced literature based on these cases yet emerged. National and regional perspectives which have shaped case studies are reliant upon Afghanistan and Iraq and finding any references to stabilisation operations beyond these two theatres is not forthcoming.1 Thus, the gap in the analytical literature is particularly acute at the level of evidence and analysis, which limits the deeper examination of the inter-linkages and interdependencies across actors and activities involved, particularly in understanding the challenges for achieving a more coherent ‘whole-of-government’ approach to future stabilisatio